The Influence of Mathematical Critical Thinking Skills Based on Students’ Math Anxiety - Nadya Alvi Rahma (Journal of Education and Learning Sciences, 2022)
This research is motivated by the low ability of students to think critically mathematically, which can be influenced by various factors. One of the causes that exist in students is the emotion and attitude towards mathematics. The many concepts that are abstract, full of numbers and full of formulas make most students think mathematics is a difficult and frightening subject. So that when faced with math lessons or math problems, students will feel anxious, afraid, restless, difficult to concentrate and avoid behavior, etc. These attitudes indicate that students experience math anxiety. This study aims to determine the effect of math anxiety and its magnitude on students' mathematical critical thinking skills. The research was conducted using a quantitative approach to the type of correlation research. The sampling technique used is probability sampling with simple random sampling. The results of the study showed that the level of mathematical anxiety in students was 58%, where mathematical anxiety had an effect on students' mathematical critical thinking skills marked by the significance value obtained, namely 0.000 <0.005 so reject H0.